THE EFFECT OF CHITOSAN SOLUTION ADDITION ON THE SIZE OF NANO CERAMIC PARTICLES IN ZrO2-Al2O3-SiO2 SYSTEM THROUGH BOTTOM-UP METHOD AS DENTISTRY RAW MATERIAL - Yanwar Faza; Zulia Hasratiningsih; Nina Djustiana; Bambang Sunendar (Journal of Health and Dental Sciences, 2022)
ABSTRACT Ceramics is a dental material used often because of its relatively good strength and aesthetic properties. Ceramics such as zirconia, alumina, and silica have different characteristics and have been synthesized using a bottom-up method separately. Recently, many studies have used chitosan solution to help synthesize nanometer-sized ceramic materials processed using the bottom-up method. This study aims to produce ZrO2-A12O3-SiO2 nanoparticle ceramics, which were synthesized simultaneously using the bottom-up method, and to see the effect of volume concentration of chitosan solution on the resulting ZrO2-A12O3-SiO2 ceramic particles. The composition ratio of ZrO2:Al2O3:SiO2 used is 3:1:1 with a concentration of 0.05M and a total volume of 500ml. The chitosan solution was added with a volume percentage of 0%, 5%, 10%, 15%, and 20%, respectively, and was named samples A, B, C, D, and E. The XRD (X-Ray Diffraction) and SEM (Scanning Electron Microscopy) characterization of the five samples showed nano-sized particles, which were 87 nm, 85 nm, 81 nm, 76 ran, and 76 nm. SEM characterization results show that sample A's particle distribution is not very visible; the particle distribution is only seen in samples B, C, D, and E, while the best particle distribution is seen in sample C. This study concludes that the optimal volume concentration of adding chitosan solution to produce nano-sized ZrO2-A12O3-SiO2 ceramics with good particle distribution is 10% by volume percentage. DOI : 10.54052/jhds.v2n2.p257-266